CONTENT, FORM AND METHODS OF USING INNOVATIVE TECHNOLOGIES IN THE EFFECTIVE ORGANIZATION OF EDUCATIONAL CLASSES - Sheraliyeva Nasiba Alimkulovna (American Journals Publishing, 2023)
Categories of purpose, content, form reveal the essence of the educational process (what it is aimed at, what it fills, what it is directed at, in what form it is completed). However, there is also another important category related to the question of how to educate in highlighting the essence of upbringing. This is a concept of the method of upbringing.
Keywords: Methods of upbringing, upbringing, types of upbringing methods, methods that serve to form social consciousness, methods of training in habituation and activity, methods of stimulation and punishment in upbringing.